The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1111/j.1600-0722.1980.tb01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Plaque inhibition and improved gingival condition by use of a stannous fluoride toothpaste

Abstract: – The present study contains data from a 4‐week clinical study where the effect of an experimental toothpaste containing 0.4% SnF2 on plaque and gingivitis was tested in a group of teenagers. The study was performed according to a double‐blind, cross‐over design. It was shown that the SnF2 containing toothpaste reduced both plaque and gingivitis significantly compared to a placebo paste which contained no fluoride or stannous ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
3

Year Published

1982
1982
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
1
10
0
3
Order By: Relevance
“…Studies have also found a positive effect from the use of SnF2 on plaque in vitro (Andres et al, 1974) and on clinical plaque levels (Konig, 1959;Tinanoff et al, 1976;Svatun et al, 1977;Ogaard et al, 1980;White and Taylor, 1979;Bay and R0lla, 1980). In this study, the lower levels for the Plaque Index in the high-Sn2+ group ( Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Studies have also found a positive effect from the use of SnF2 on plaque in vitro (Andres et al, 1974) and on clinical plaque levels (Konig, 1959;Tinanoff et al, 1976;Svatun et al, 1977;Ogaard et al, 1980;White and Taylor, 1979;Bay and R0lla, 1980). In this study, the lower levels for the Plaque Index in the high-Sn2+ group ( Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have reported that frequent application of high concentration fiuorides may reduce gingivitis (Ringelberg 1979, Bay & Rolla 1980, Leverett et al 1984. Some suggest that amine fiuoride and stannous fiuoride may be particularly effective against plaque microorganisms (Muhlemann 1983, Tinanoff 1985, Newman et al 1985.…”
Section: Fluoridesmentioning
confidence: 99%
“…been unsuccessful because of incompatibility Since daily mechanical removal of plaque by with some of the normal dentifrice ingredi-ents (8), A recent study (9) has confirmed that a 0.8% chlorhexidine (CHX) dentifrice, although it exhibited some ability to reduce plaque, was less effective than a 1% GHX gel. Other recent studies have shown that metal salts such as stannous fluoride and zinc citrate retain their antiplaque activity when incorporated into dentifrices (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%